2016
DOI: 10.1186/s13059-016-1028-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of tumor immunity: implications for cancer immunotherapy

Abstract: BackgroundUnderstanding the interactions between tumor and the host immune system is critical to finding prognostic biomarkers, reducing drug resistance, and developing new therapies. Novel computational methods are needed to estimate tumor-infiltrating immune cells and understand tumor–immune interactions in cancers.ResultsWe analyze tumor-infiltrating immune cells in over 10,000 RNA-seq samples across 23 cancer types from The Cancer Genome Atlas (TCGA). Our computationally inferred immune infiltrates associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,744
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,942 publications
(1,773 citation statements)
references
References 42 publications
26
1,744
1
2
Order By: Relevance
“…Nevertheless, the data together with the genomic data as described above illustrate that different cancer types may differ not only by genetics but also by their organ-specific immunologic microenvironments. Consistent with these data, a recent paper integrated the molecular profiles of over 10,000 tumor samples across 23 cancer types and found that the intertumor heterogeneity of immune infiltration may be caused by both cancer genetic variations as well as the disease-specific expression pattern of the chemokine/receptor network (41).…”
Section: The Organ-specific Immune System Differs In Different Humanmentioning
confidence: 68%
“…Nevertheless, the data together with the genomic data as described above illustrate that different cancer types may differ not only by genetics but also by their organ-specific immunologic microenvironments. Consistent with these data, a recent paper integrated the molecular profiles of over 10,000 tumor samples across 23 cancer types and found that the intertumor heterogeneity of immune infiltration may be caused by both cancer genetic variations as well as the disease-specific expression pattern of the chemokine/receptor network (41).…”
Section: The Organ-specific Immune System Differs In Different Humanmentioning
confidence: 68%
“…2022 A recent study using in silico analysis of tumor immunity also underpinned this conclusion, when taking patient age and stage into consideration. 23 …”
Section: Discussionmentioning
confidence: 99%
“…We used TCGA RNA sequencing (RNA-seq) data sets and TIMER (32) to examine the relevance of the CRIPSR screen (fig. S8) and PBAF complex in human cancers.…”
Section: Clinical Relevance Of Pbaf Complex To Tumor Immunitymentioning
confidence: 99%
“…Volcano plot showing the Spearman’s correlation and estimated significance of ARID2 (left) or PBRM1 (right) with GZMB mRNA levels from RNA-seq data across TCGA cancer types calculated by TIMER (Tumor Immune Estimation Resource) and adjusted for tumor purity (32). Each dot represents a cancer type in TCGA; red dots indicate significant correlations ( P < 0.01).…”
Section: Figmentioning
confidence: 99%